Identification of Mendel's White Flower Character - Hellens, Roger P.; Moreau, Carol; Lin-Wang, Kui; Schwinn, Kathy E.; Thomson, Susan J.; Fiers, Mark W. E. J.; Frew, Tonya J.; Murray, Sarah R.; Hofer, Julie M. I.; Jacobs, Jeanne M. E.; Davies, Kevin M.; Allan, Andrew C.; et al. (PLOS ONE, 2010)
Background The genetic regulation of flower color has been widely studied, notably as a character used by Mendel and his predecessors in the study of inheritance in pea. Methodology/Principal Findings We used the genome sequence of model legumes, together with their known synteny to the pea genome to identify candidate genes for the A and A2 loci in pea. We then used a combination of genetic mapping, fast neutron mutant analysis, allelic diversity, transcript quantification and transient expression complementation studies to confirm the identity of the candidates. Conclusions/Significance We have identified the pea genes A and A2. A is the factor determining anthocyanin pigmentation in pea that was used by Gregor Mendel 150 years ago in his study of inheritance. The A gene encodes a bHLH transcription factor. The white flowered mutant allele most likely used by Mendel is a simple G to A transition in a splice donor site that leads to a mis-spliced mRNA with a premature stop codon, and we have identified a second rare mutant allele. The A2 gene encodes a WD40 protein that is part of an evolutionarily conserved regulatory complex.